Analysis of a New Reduced Switch Nine Level Inverter - C.R. Balamurugan; S.P. Natarajan; R. Bensraj (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The multi level inverter system is mostly used in ac drives, when both reduced harmonic contents and high power are required. In this paper a new topology of multilevel inverter is introduced. This type has many steps with less power electronic switches. Due to the less number of switches the cost of the inverter is very less and also less installation area is required. Firstly, we describe briefly the structural parts of the inverter then switching strategy and operational principles of the proposed inverter are explained and operational topologies are given. Simulation is performed using MATLAB SIMULINK. Various PWM techniques are applied to the circuit such as PDPWM, PODPWM, APODPWM, VFPWM and COPWM. By comparing among the PWM techniques, PODPWM provide the less THD value and COPWM provide a higher fundamental RMS output voltage.